Evaluation of the Air Quality Index and its Environmental Impacts on Residents of Fallujah City - Al- Rikabi, Raya; Al-Qurra lucy, Hanan; Al-Maliki, Maitham (Al-Adab Journal, 2025)
Rapid urbanization contributes to increasing the concentrations of pollutants in the surrounding air, and this is clearly evident after applying the linear equation for the air quality index in Fallujah city, as the air quality index values ​​for total suspended particles ranged between the good and very dangerous categories (AQI = 0 -500) for the two seasons, while the air quality index values ​​for particles with a size of (PM2.5) ranged between the moderate category and the very dangerous category (AQI = 51 -500) for January, while the index values ​​ranged between the moderate and dangerous categories (AQI = 51-300) for July, and the air quality index values ​​for particles with a size of (PM10) ranged between moderate and very dangerous (AQI = 51 -500) for January, while the index values ​​ranged between the good and dangerous categories (AQI = 0-300) for July. Among the health effects that accompanied the high index lie in the reduction of tolerance in healthy people and the appearance of negative symptoms in people with allergies, but if the index values ​​are greater than 500, it can lead to deaths in sick people and elderly people. The index values ​​vary depending on the variation in human activities and the type of fuel used in Fallujah city.